Manajemen Layanan Mutu Akademik Dalam Meningkatkan Daya Saing Lulusan Pada STAI Di Jawa Barat - Rusmadi (ISLAMICA, 2020)
The background of this research is the competition for quality and quantity among institution of higher education which has been very competitive in recent decades, encouraging universities to remain of high quality, both in the individuals’ sight within internal environment and by external people outside. The purpose of this study is to describe the Planning, Implementation, Evaluation, Obstacles and Solutions for solving academic quality service problems in improving the competitiveness of graduates at STAI in West Java. The main theory in this study is based on six value systems, management and TQM. This study applies a qualitative approach toward the case study method. The Efforts in improving the quality of STAI's academic services can be seen from the quality of higher education academic planning by taking strategic steps including forming teams, collecting data (diagnosis), formulating strategic plans (laying philosophical basis, formulating vision and mission, formulating goals and values, analyzing the situation, formulating of strategic policies, formulating of long-term development plans, formulating of financing strategies, and formulating of strategic controls), discussion, and socialization. Establishment of organizations / work units assigned to carry out, evaluate, and improve the implementation of academic quality. Then it is followed by the placement of personnel who are qualified and capable to carry out the task. The unit or institution / body formed will then formulate quality documents. The evaluation used to improve the quality of STAI is the internal quality evaluation of university. The efforts to improve quality focus on programs such as improving lecturer qualifications, structuring evaluations and accreditation. In terms of improving the quality of planning and budgeting, in addition to making improvements such as self-evaluation standards, it also includes evaluating learning outcomes, and conducting socialization.